Sphingolipid and Trimethylamine-N-Oxide (TMAO) Levels in Women with Obesity after Combined Physical Training - Brandao, Camila Fernanda Cunha; Krempf, Michel; de Carvalho, Flávia Giolo; Aguesse, Audrey; Junqueira-Franco, Márcia Varella Morandi; Batitucci, Gabriela [UNESP]; de Freitas, Ellen Cristini [UNESP]; Noronha, Natalia Yumi; da Silva Rodrigues, Guilherme; Junqueira, Gizela Pedroso; Borba, Diego Alcantara; Billon-Crossouard, Stéphanie; et al. (MDPI, 2024)
Obesity causes metabolic changes, such as the development of cardiovascular diseases. Moreover, physical exercise promotes protection against these diseases. Thus, the objective of the present study was to evaluate whether combined physical training can improve the metabolic system of women with obesity, reducing plasma concentrations of trimethylamine N-oxide (TMAO) and sphingolipids, regardless of weight loss. Fourteen obese women (BMI 30-40 kg/m2), aged 20-40 years, sedentary, were submitted to 8 weeks of combined physical training (strength and aerobic exercises). The training was performed three times/week, 55 min/session, at 75-90% maximum heart rate. All participants were evaluated pre- and post-exercise intervention, and their body composition, plasma TMAO, creatinine, lipid profile, and sphingolipid concentrations were recorded. Maximum oxygen consumption (VO2max), Speed lactate threshold 1 (SpeedLT1), and Speed lactate threshold 2 (SpeedLT2) evaluated physical performance. Results: After combined exercise, it did not change body composition, but TMAO, total cholesterol, and sphingolipid concentrations significantly decreased (p < 0.05). There was an increase in physical performance by improving VO2max, SpeedLT1, and SpeedLT2 (p < 0.05). The combined physical exercise could induce cardiovascular risk protection by decreasing TMAO in obese women, parallel to physical performance improvement, independent of weight loss.